Probing archaeal cell biology: exploring the use of dyes in the imaging of Sulfolobus cells - Cezanne, Alice; Hoogenberg, Baukje; Baum, Buzz (Frontiers in Microbiology, 2023)
Archaea are key players in many critical ecological processes. In comparison to eukaryotes and bacteria, however, our understanding of both the cell biology and diversity of archaea remains limited. While archaea inhabit a wide range of environmental conditions, many species are extremophiles, surviving in extreme temperature, salt or pH conditions, making their cell biology hard to study. Recently, our understanding of archaeal cell biology has been advanced significantly by the advent of live cell imaging in extremis as well as the development of genetic tools to exogenously express fluorescent proteins in some mesophilic archaeal model systems e.g., Haloferax volcanii. However, for most archaeal species, especially thermophilic species or emerging model systems without well characterized genetic tools, live cell imaging remains dependent on fluorescent chemical probes to label and track the dynamics of living cells. While a wide range of fluorescent stains and markers that label different components of the cell are available commercially, their use has usually been optimized for use in a small number of eukaryotic cell systems. Here we report the successes and failures of the application of membrane, DNA, S-layer and cytoplasm markers in live cell imaging of archaea, as well as the optimization of fixation and immunolabelling approaches. We have applied these markers to the thermoacidophilic archaeon Sulfolobus acidocaldarius, but expect some to work in other archaeal species. Furthermore, those procedures that failed in S. acidocaldarius may still be used for imaging archaea that grow at a more neutral pH and/or at a less extreme temperature.